A new class of battery-free, mechanically powered, piezoelectric Ca5Ga6O14:Tb3+ phosphors with self-recoverable luminescence. Issue 25 (13th June 2022) - Hu, Tao; Gao, Yan; Wang, Bo; Yu, Ting; Wen, Dawei; Cheng, Yao; Zeng, Qingguang
Abstract : A new class of Ca5 Ga6 O14 :Tb 3+ mechanoluminescent phosphors with trap-independent, self-recoverable mechanoluminescence and a low mechanical stimulus threshold are reported, whose properties originate from piezoelectricity of the host with giant piezoelectric coefficients. Abstract : Mechanoluminescent (ML) phosphors, which are capable of converting mechanical energy into photons, are of great interest in a wide range of fundamental applications. However, most of the discovered ML phosphors are limited to trap-controlled types, hindering them from operating in fields where dark working conditions are required since the recovery of the ML intensity needs light re-irradiation. Herein, a mechanically powered Ca5 Ga6 O14 :Tb 3+ phosphor, featuring trap-independent, self-recoverable mechanoluminescence, and a low mechanical stimulus threshold, is reported. Systematic experimental and theoretical studies are performed to reveal the origin of the mechanoluminescence, demonstrating that the mechanoluminescence is dictated by piezoelectricity as a result of the non-centrosymmetric mm 2 point group of the Ca5 Ga6 O14 host. Density functional perturbation theory (DFPT) is used to study the piezoelectric properties, and due its polar structure, the host possesses giant piezoelectric coefficients with d ij and e ij as high as 4.417 pm V −1 ( d 24 ) and 1.27 × 10 −10 C m −2 ( e 31 ), respectively, which are comparable to or even higher than those of many frequently used piezoelectric materials. Owing to these admirable ML properties, the newly found Ca5 Ga6 O14 :Tb 3+ phosphor has the potential for battery-free, energy-saving piezo-photonic applications.